2000
DOI: 10.1258/002367700780387750
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal fentanyl compared with parenteral buprenorphine in post-surgical pain in swine: a case study

Abstract: SummaryThe use of pigs as research animals in survival surgery has increased greatly in the last 15 years. Personnel conducting pig research have been hampered by a lack of proven longacting analgesics for treatment of surgical pain of longer duration, and bya lack of reliable non-subjective parameters for the assessment of pain relief. The efficacy of the mixed opioid agonist-antagonist buprenorphine hydrochloride 0.10 mg/kg pm (n = 2) in the treatment of post-thoracotomy pain was compared with that of a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 14 publications
1
47
0
Order By: Relevance
“…Harvey-Clark et al (2000) reported that the pain control produced by transdermal fentanyl patches, with a serum concentration range of 0.3-0.6 ng/mL, is comparable to the analgesia produced by buprenorphine in pigs. During this 48 h period, a lower incidence of active behaviours was noted in Group M and in Group P. This inactivity would be caused by a combination of a postoperative passive state and a depressant effect of opioids, as suggested by Harvey-Clark et al (2000). Fentanyl, a synthetic opioid acting on mu receptors, is responsible for some side effects such as inactivity (Rang et al 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Harvey-Clark et al (2000) reported that the pain control produced by transdermal fentanyl patches, with a serum concentration range of 0.3-0.6 ng/mL, is comparable to the analgesia produced by buprenorphine in pigs. During this 48 h period, a lower incidence of active behaviours was noted in Group M and in Group P. This inactivity would be caused by a combination of a postoperative passive state and a depressant effect of opioids, as suggested by Harvey-Clark et al (2000). Fentanyl, a synthetic opioid acting on mu receptors, is responsible for some side effects such as inactivity (Rang et al 1996).…”
Section: Discussionmentioning
confidence: 97%
“…The main purpose of the present study was to determine whether epidural morphine and fentanyl patch would provide analgesia after abdominal surgery. The means of administration were chosen to avoid Laboratory Animals (2006) 40 frequent animal handling, since repeated administration of drugs is also stressful to pigs (Harvey-Clark et al 2000). Further, non-steroidal anti-inflammatory drugs (NSAIDs) which are frequently used for postoperative analgesia (Nolan 2001) were not used, since these pigs were going to be included in experimental infection studies.…”
Section: Discussionmentioning
confidence: 99%
“…Feed intake was used to assess the benefit of ketoprofen compared with flunixin or untreated grower pigs experimentally infected with Actinobacillus pleuropneumoniae (108), and altered feed intake (using a 4-point scale in which 1 indicated no change and 4 inappetance) was used as part of a clinical index score to assess the efficacy of meloxicam in the treatment of sows with mastitis–metritis–agalactia (MMA) (109). Food consumption decreased after thoracotomy surgery in pigs (110), and time spent feeding has been used to assess the efficacy of pain mitigation strategies in pigs undergoing abdominal surgery (111) and a femoral fracture model (112). In a study using a feed reward collection test to assess sows’ motivation to obtain feed rewards with different levels of lameness, moderately and severely lame sows obtained fewer rewards than mildly and non-lame sows (113).…”
Section: Pain Assessment In Pigsmentioning
confidence: 99%
“…The existing knowledge is based primarily on studies of post-surgical pain, describing how pigs respond differently to acute and prolonged pain, in which the former typically triggers vocalization and escape responses. In contrast, signs of prolonged pain are described as more discrete, for example, inactivity, abnormal behaviour, postural changes or reluctance to change posture (Harvey-Clark et al, 2000). The Danish Veterinary and Food Administration (Anonymous, 2007) has stated, however without any data, that sows with shoulder ulcers may show difficulties in getting up and that they express pain when touched.…”
Section: Welfare Consequences Of Decubital Shoulder Ulcersmentioning
confidence: 99%